The Baloch… Glimpses Of Social and Martial Traditions - Bakht, Dr,Naudir (Hanken, 2009)
This paper focuses upon the social and martial traditions of the Balochs. It is an effort to dig out the classical Baloch traditions and to carry them to the youth with a massage that they should remember their glorious past and the traditions their forefather had. These traditions can evidently be witnessed in the Baloch nomadic and rural life and provide food for thought for the contemporary researchers.